Analysis of energy poverty in the Republic of Croatia - Andrea Babić; Dubravka Maras (Mednarodno Inovativno Poslovanje)
For a long time, energy has been a fundamental element of human growth and development. However, despite all technological progress and information development, many people in the world still do not have consistent access to at least one form of energy. This is where the concept of energy poverty appears. Energy poverty is generally defined as a situation in which households do not have enough disposable income to pay the bills for the energy needed in their household. The main factors that influence the appearance of energy poverty are primarily insufficient household incomes, the energy prices and their availability in a particular area, and the quality of housing units. This paper tries to show what the situation is in the Republic of Croatia and how to approach solving this problem. In the Republic of Croatia, this problem is tried to be solved by defining the vulnerable energy buyers, which places energy poverty in social policy, and accordingly, measures are most often implemented in the form of financial benefits (it is equated with energy poverty). What is missing here is the important connection between energy and social policy.